CircLONP2 Accelerates Esophageal Squamous Cell Carcinoma Progression via Direct MiR-27b-3p-ZEB1 Axis - Zhu, Cailin; Bi, Weiyun; Li, Hongtao; Wang, Wen (Frontiers in Oncology, 2022)
Circular RNAs (CircRNAs) are important mediators in ESCC carcinogenesis. We aim to explore the functions and mechanisms of circLONP2 in ESCC progression. CircLONP2 level was evaluated in ESCC samples and cell lines. The role and mechanisms of circLONP2 in ESCC proliferation and migration were demonstrated in vitro. We found that circLONP2 was upregulated in human ESCC and predicts poor OS and DFS. CircLONP2 promotes ESCC aggressiveness through directly interacting with miR-27b-3p, thus upregulating the expression levels of its target gene ZEB1 through suppressing miR-27b-3p activity. Therefore, we demonstrated that circLONP2/miR-27b-3p/ZEB1 axis promote ESCC metastasis via regulating EMT related proteins. CircLONP2 may serves as an oncogenic circRNA and as a prognostic biomarker in ESCC progression.